2015
DOI: 10.1111/oik.02106
|View full text |Cite
|
Sign up to set email alerts
|

Light and nutrients regulate energy transfer through benthic and pelagic food chains

Abstract: The amount of energy flowing to top trophic levels depends on primary production and the efficiency at which it is converted to production at each trophic level. In aquatic systems, algal production is often limited by light and nutrients, and the nutritional quality of algae depends on the relative balance of these two resources. In this study, we used a mesocosm experiment to examine how light and nutrient variation affected food chain efficiency (FCE, defined as the proportion of primary production converte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
43
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(50 citation statements)
references
References 59 publications
(98 reference statements)
3
43
4
Order By: Relevance
“…In addition, in contrast to several previous studies (Malzahn et al, 2007;Boersma et al, 2008;Dickman et al, 2008;Rowland et al, 2015), we found no strong evidence to support a carryover effect of food quality to carnivores, i.e. Interestingly, we found differential support for the role of food quantity and quality as potential drivers of carnivore production.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…In addition, in contrast to several previous studies (Malzahn et al, 2007;Boersma et al, 2008;Dickman et al, 2008;Rowland et al, 2015), we found no strong evidence to support a carryover effect of food quality to carnivores, i.e. Interestingly, we found differential support for the role of food quantity and quality as potential drivers of carnivore production.…”
Section: Discussioncontrasting
confidence: 99%
“…Previous experiments in these mesocosms have reported similar difficulty in collecting zooplankton for body nutrient analysis (Dickman et al, 2008;Rowland et al, 2015). Previous experiments in these mesocosms have reported similar difficulty in collecting zooplankton for body nutrient analysis (Dickman et al, 2008;Rowland et al, 2015).…”
Section: Chlorophyll and Nutrient Analysesmentioning
confidence: 80%
See 3 more Smart Citations